2023
DOI: 10.1093/brain/awad213
|View full text |Cite
|
Sign up to set email alerts
|

CSF proteomics in autosomal dominant Alzheimer’s disease highlights parallels with sporadic disease

Emma L van der Ende,
Sjors G J G In ‘t Veld,
Iris Hanskamp
et al.

Abstract: Autosomal dominant Alzheimer’s disease (ADAD) offers a unique opportunity to study pathophysiological changes in a relatively young population with few comorbidities. A comprehensive investigation of proteome changes occurring in ADAD could provide valuable insights into AD-related biological mechanisms and uncover novel biomarkers and therapeutic targets. Furthermore, ADAD might serve as a model for sporadic AD, but in-depth proteome comparisons are lacking. We aimed to identify dysregulated CSF proteins in A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 93 publications
0
10
0
Order By: Relevance
“…REG4 was recognized as the top-ranked CSF immune activation marker predicting CDR conversion independently of other factors in cognitively unimpaired elderly. However, there were no apparent differences in CSF REG4 levels between control and MCI/AD subjects in other cohorts ( 55 , 56 ). CSF REG4 was up-regulated in AD compared to non-AD dementia cases including dementia with Lewy bodies and frontotemporal dementia ( 55 ).…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…REG4 was recognized as the top-ranked CSF immune activation marker predicting CDR conversion independently of other factors in cognitively unimpaired elderly. However, there were no apparent differences in CSF REG4 levels between control and MCI/AD subjects in other cohorts ( 55 , 56 ). CSF REG4 was up-regulated in AD compared to non-AD dementia cases including dementia with Lewy bodies and frontotemporal dementia ( 55 ).…”
Section: Discussionmentioning
confidence: 71%
“…Among the 85 immune activation markers associated with CDR conversion in our cohort with P values < 0.05 in unadjusted analysis, CSF levels of WNT9A, IL-6, and CXCL6 were altered in MCI cases with amyloid pathology compared to control groups ( 55 ). While higher CSF levels of MMP10, TNFSF13, ANGPTL4, LTBR, WNT9A, CD4, FLT3LG, CD84, MICB_MICA, and CCL23 were detected in AD cases than control groups in the 85 immune activation markers ( 55 ), another study also found the increases of MMP10, TNFSF13, and CD4 in CSF from autosomal dominant AD ( 56 ).These observations indicate that some CSF immune activation markers start changing even at presymptomatic early stages of cognitive impairment. REG4 was recognized as the top-ranked CSF immune activation marker predicting CDR conversion independently of other factors in cognitively unimpaired elderly.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This will be facilitated by an increased exploitation of fluid markers including plasma and cerebrospinal fluid for both diagnosis and therapeutic validation. 4952…”
Section: Discussionmentioning
confidence: 99%
“…These studies revealed pathophysiological mechanisms such as synapse loss and neuroinflammation linked to immune, vascular, metabolic and extracellular matrix (ECM) dysfunction. Furthermore, integrated analyses across brain and biofluids demonstrated a significant overlap between brain network changes and the CSF proteome in AD, enabling early disease prediction even in the preclinical phase of AD 12, 14-16 . For example, CSF proteomic measurements in autosomal dominant AD (ADAD) that overlap with brain protein co-expression modules were recently used to define the evolution of AD pathology over a timescale spanning six decades 17 .…”
Section: Introductionmentioning
confidence: 99%